An Analysis of Speech Acts Used in The Witches Novel by Roald - Ni Komang Julia Dewi (STKIP AGAMA HINDU SINGARAJA, 2022)
This research was descriptive qualitative research. The present research studied the speech acts types produced by the characters in the witches novel. The research subject was the novel itself, and the objects were focused on the speech act types and the functions or points. The witches novel is a novel intendedfor children with the theme of loss and fantasy. There are 305 utterance produced by the characters from the novel which are analyzed by speech acts. The obtained data were analyzed descriptively and categorically based on Searle's theory of speech acts. The analysis concluded that from the 5 types ofspeech acts according to Searle's theory, there were four of them used in the witches novel. Namely, representative, directive, expressive and commisive act.